If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -3)(x + 7) = 0 Reorder the terms: (-3 + 3x)(x + 7) = 0 Reorder the terms: (-3 + 3x)(7 + x) = 0 Multiply (-3 + 3x) * (7 + x) (-3(7 + x) + 3x * (7 + x)) = 0 ((7 * -3 + x * -3) + 3x * (7 + x)) = 0 ((-21 + -3x) + 3x * (7 + x)) = 0 (-21 + -3x + (7 * 3x + x * 3x)) = 0 (-21 + -3x + (21x + 3x2)) = 0 Combine like terms: -3x + 21x = 18x (-21 + 18x + 3x2) = 0 Solving -21 + 18x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-7 + 6x + x2) = 0 Factor a trinomial. 3((-7 + -1x)(1 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-7, 1}
| x+(x-11)=73 | | 7w+6w=25 | | 3(6n-1)=123 | | -5+25-r=25 | | m/10=19 | | -21=c/3 | | -3-6x=-51 | | 6a+7b=69 | | 42/0.4 | | -10=5/6n-7-1/3n | | l+3+4xw= | | 2(p+13)+7=8(5-p)-3(-7-3p)+4 | | n/19=16 | | 1.6x-1.3x-1=8 | | X-30=125 | | (-4x+11)= | | 3(2a+b-3c)= | | (x+4)+(3x-7)= | | k/2=-20 | | (2x+10)2=(3x-55)2 | | -1+3.3h=-16 | | (8x)0(8x)= | | 50+6m= | | 9+x=-8x-18 | | X=50-46 | | (2x^3-2/7)^3 | | 3y+3+2y+6=10y-31 | | -9+3n=-63 | | g(n)=25-49(n-1) | | k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x |